Removal of heavy metals from wastewater using low-cost biochar prepared from jackfruit seed waste - Husni Ibrahim (Tanjung Malim, 2023)
Removal of heavy metals from wastewater using low-cost biochar prepared from jackfruit seed waste by Husni Ibrahim